Constitutively Activating GNAS Somatic Mutation in Right Ventricular Outflow Tract Tachycardia. (30th September 2021) - Ip, James E.; Xu, Linna; Dai, Jie; Steegborn, Clemens; Jaffré, Fabrice; Evans, Todd; Cheung, Jim W.; Basson, Craig T.; Panaghie, Gianina; Krogh-Madsen, Trine; Abbott, Geoffrey W.; Lerman, Bruce B.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: The cellular mechanism of focal, idiopathic right ventricular outflow tract (RVOT) tachycardia is thought to be due to cAMP-mediated triggered activity. A potential molecular mechanism has not yet been determined. We identified and characterized a novel missense somatic mutation in the gene (GNAS) encoding the Gs α (stimulatory G protein alpha-subunit) from a patient with RVOT tachycardia that is proposed to be the etiology of the clinical tachycardia. Methods: Percutaneous endomyocardial biopsies were obtained from multiple sites in a patient with nonexertional, repetitive monomorphic RVOT tachycardia. Sequencing of extracted genomic DNA identified a Gs α W234R variant only at the site of tachycardia origin. Functional studies using in vitro transfection with S49 cyc− murine lymphoma cells and measurement of cyclic AMP levels were performed. A trypsin protection assay assessed GTP binding kinetics and structural modeling predicted the impact of the mutation on protein-protein interactions. Whole-cell patch clamp experiments of transfected CHO cells assessed the downstream effects of the mutation. Results: In vitro studies of the GNAS mutation (W234R) demonstrated basal levels of cAMP ≈16-fold higher than wild-type cells, consistent with constitutive stimulation of Gs α. Mutant Gs α was partially protected from proteolysis after incubation with GTP, indicating diminished GTPase activity and reduced GTP hydrolysis as the mechanism for increased basal intracellular cAMP levels. Transfected mutant CHO cells increased unstimulated mean peak L-type calcium channel current density by ≈50% and in silico modeling demonstrated spontaneous delayed afterdepolarizations and triggered activity. Conclusions: We identified a novel somatic mutation in GNAS associated with RVOT tachycardia. The mutation results in constitutive activation of Gs α, impairs GTP hydrolysis, and elevates basal cAMP levels, leading to enhanced L-type calcium current and triggered activity. These findings confirm that RVOT tachycardia can be caused by somatic mutations in signal transduction proteins that regulate intracellular cAMP and its downstream effectors.